POST-PANDEMIC ECONOMIC RECOVERY: A STUDY OF WOMEN BREADWINNERS IN LOCAL TRADITIONAL CEREMONIES IN GADUR COMMUNITY PADANG PARIAMAN, WEST SUMATRA - Tasrif, Nurhairunnisa (TASAMUH, 2022)
This study shows systematically the struggles of women breadwinners in the process of post-pandemic economic recovery in Gadur community, Padang Pariaman, West Sumatra. The breadwinners, who are mostly women, are accustomed to making a living from various activities such as; social activities, wedding and death traditions where they usually make Malamang, Baralek, Bajambang, and a series of folk parties. This study aims to see further [1] how is the economic recovery process of the Gadur community (women breadwinners) in post-pandemic, [2] how do they respond and survive in the midst of the economic crisis during the pandemic that has an impact on their income, [3] how do local traditions become a source of livelihood for women in Gadur. As qualitative research, the data collection method used in-depth interviews with people who were directly involved in the local traditional ceremonies, especially women/housewives. Some of the research findings include; [1], despite the community was experiencing economic difficulties due to the pandemic, the women breadwinners in Gadur were able to survive and get through it by taking advantage of several celebrations held during the pandemic. [2], In the culture of Gadur community, local traditions such as social activities (com pensation for orphans and dhuafa), weddings and death traditions that are colored by Malamang (memasak lemang) Baralek, and Bajambang (makan barapak/bersama) activities have returned as a source of livelihood. [3], Post-pandemic recovery helps to improve the income of the community through socio-religious and local traditional activities in Gadur, Padang Pariaman, West Sumatra.